2020
DOI: 10.3389/fonc.2020.00812
|View full text |Cite
|
Sign up to set email alerts
|

Back-Splicing Transcript Isoforms (Circular RNAs) Affect Biologically Relevant Pathways and Offer an Additional Layer of Information to Stratify NMIBC Patients

Abstract: Circularized transcript isoforms due to back-splicing are increasingly being reported in different tissues types and pathological states including cancer. Since these circular RNAs (circRNAs) are more stable than linear messenger RNA their identification and profiling in tumor tissue could aid in stratifying patients and may serve as biomarkers. In this study, we have investigated the relationship between circRNA expression and tumor grade in a cohort of 58, mostly non-muscle-invasive bladder cancer patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Regarding PDCD1LG2 (PD-L2) gene expression in UBC, we utilised RNA-seq data from our own analysis of 44 NMIBCs ( 18 ). These data confirmed expression of PDCD1LG2 (PD-L2) in addition to CD274 (PD-L1), although no effect of tumor grade was evident on expression of either gene in this small cohort ( Figures 2A, B ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding PDCD1LG2 (PD-L2) gene expression in UBC, we utilised RNA-seq data from our own analysis of 44 NMIBCs ( 18 ). These data confirmed expression of PDCD1LG2 (PD-L2) in addition to CD274 (PD-L1), although no effect of tumor grade was evident on expression of either gene in this small cohort ( Figures 2A, B ).…”
Section: Resultsmentioning
confidence: 99%
“…Gene Ontology (GO) includes biological process classification (BP), cellular component (CC), and molecular function classification (MF). Some studies have pointed out that circRNAs may affect the expression of its parental genes, so the function of circRNAs may be related to the function of its parental gene ( Bolisetty and Graveley, 2013 ; Boeckel et al, 2015 ; Goel et al, 2020 ; Mehta et al, 2020 ). Here, the function of the parental gene is used as a prediction of the function of circRNAs.…”
Section: Resultsmentioning
confidence: 99%
“… 34 , 35 , 36 Of note, some researchers verified the dysregulation of circRNAs in urine of bladder cancer patients. 37 , 38 , 39 Therefore, with the consideration of the characteristics and accessibility of circRNAs, they are suitable for clinical diagnosis and prognostic prediction in human cancers. Chen and his colleagues 40 found that hsa_circ_0000190 has better sensitivity and specificity for a gastric cancer diagnosis compared to carcinoembryonic antigen (CEA) and CA19-9 (classic biomarkers of gastric cancer).…”
Section: Discussionmentioning
confidence: 99%